Partial immune responses in Sichuan bream (Sinibrama taeniatus) after starvation - Shi, Jinfeng; Zhuo, Dayou; Lu, Minfang; Wang, Haoyu; Gu, Haoran; Liu, Xiaohong; Wang, Zhijian (Frontiers in Immunology, 2023)
Background Food deprivation is a severe stress across multiple fields and it might be a challenge to immune system. Methods In the present study, adult male Sinibrama taeniatus were deprived of feed for 7 to 28 days. We explored the effects of starvation on immunity in S. taeniatus through hematological analysis, antioxidant capacity analysis, detection of the content or activity of immune factors in plasma, and transcriptomic analysis. Results The results indicated that biometric indexes significantly decreased in the fish after starvation, the proportion of thrombocyte, neutrophil and monocyte increased and, conversely, the proportion of lymphocyte decreased. The antioxidant indexes (SOD and CAT) and innate immune parameters (LZM, C3) were upregulated in fish suffering from a short period of starvation, while adaptive immune parameter (IgM) conversely declined. The transcriptome analysis revealed the changes of various metabolic regulatory pathways involved in fatty acids and amino acids, as well as the immune responses and antioxidant capacity. Conclusions Taken together, this research in the present study suggested an induced innate immunity while a partly suppressed adaptive immunity under a short period starvation.